Realising a system of coupled microgrid networks using single‐phase interconnection lines. Issue 3 (23rd March 2021) - Ferdous, S. M.; Shahnia, Farhad; Shafiullah, GM
Abstract: Overloading and renewable‐based excessive generation are a frequently observed phenomena in an autonomously operating islanded microgrid (MG) which will lead to unacceptable voltage or frequency deviation in the MG. Such problems can be alleviated by mechanisms such as load shedding or curtailment of renewable sources. Alternatively, coupling the neighbouring MGs and enabling a provisional power exchange amongst them can improve the situation more effectively. The power exchange link between the MGs can be in the form of a conventional three‐phase ac line but a single‐phase ac link is more cost‐effective, especially considering the amount of the power that needs to be transferred through this link. This approach requires power electronics‐based converters to convert a three‐phase ac MG into a single‐phase power exchange link and control the power sharing amongst them. The same is needed when the MGs have to be coupled while maintaining their autonomy, but the corresponding costs of the single‐phase system are less. This article has proposed a decentralised approach to control and couple the neighbouring MGs to realise provisional power exchange through such a structure. The performance of the proposed control mechanism is evaluated through simulation studies in PSIM ®, and its sensitivity and stability are analysed against its key design and operational factors.